PENGEMBANGAN BUKU PANDUAN KELUARGA ADIL GENDER UNTUK MENCEGAH KEKERASAN DALAM RUMAH TANGGA - Siti Rohmah Nurhayati; Siti Partini; Sigit Sanyata (LPPM UNY, 2009)
The aim of this study was to producing gender equality family guidelines book. Especially the aim of the study in the first year were to 1) identify spouse comprehension of gender and gender equality; 2) identify realization of gender equality in family; 3) identify spouse comprehension of domestic violence; 4) need assessment of gender equality family guidelines book; and 5) design a gender equality family guidelines book. The study has using Borg and Gall research and development approach. Three research steps is conducted in the first year, were: 1) preface studied and collected information about data which needed to develop product; 2) planned (concept defined, goal formulated, and determined the book provide organized; 3) developed the initial product (prepared the book subject matter, and arranged the book). The Subject of the preface study were 260 spouse. Population in the study were spouse who lived in Daerah Istimewa Yogyakarta. Sample taking was purposive stratified area sampling. The instrument of the study were gender and gender equality comprehension test, domestic violence comprehension test, gender equality realization in family questionnaire and need assessment questionnaire. The result of this study showing that 1) spouse comprehension of gender and gender equality was low; 2) realization of gender equality in family was unbalanced; 3) spouse comprehension of domestic violence was low; 4) there was a need of guidelines book which used to guiding to realize gender equality in family that content subject matter as gender, gender inequality, gender equity, and application of gender equality in family